Między światami. Poszukując kształtu rzeczywistości po antropocenie - Maciej Kijko (Załącznik Kulturoznawczy)
The purpose of the article is to highlight the serious challenge of living in the Anthropocene era. Recognizing humans as a force of geological significance, it is also necessary to take into account our responsibility for the state of the world and the search for ways to adequately deal with the threat posed by the deepening degradation of the planet, which is ultimately likely to lead to the disappearance of the human and many other species. One way to deal with the danger is to change the way we describe the situation and find a new language for expressing our new attitude to reality. The path proposed in the text is to step out of the framework of the Western perspective and look to numerous indigenous visions of the world for ways of thinking about, describing, and existing in the world that are different from the one that led to the catastrophe.